Eight meditations on musical signification - Griffiths, Lee (Jazz Research Journal, 2023)
In this article I offer eight short meditations (or perhaps provocations) on the theme of musical signification. They each cover a different theme—composition, rehearsal, sung and spoken words, writing about music, improvisation, cultural politics, technology, and listening to music—with the aim of evoking a rich and multidimensional sense of musical meaning. Their form and style are influenced by my reading of the diffractive philosophy of Karen Barad and are meant to invite a creative reading of the eight sections through one another.